Principles and problems of policy implementation reconsiderations for effective secondary school administration - Akporehe, Dorah Ataphia; Comfort, Osiobe; Egoh, Blessing (Intelektual Pustaka Media Utama, 2024)
Policy implementation has presented the Nigerian educational system with countless obstacles cum problems. This research explored the principles and problems of policy implementation reconsiderations for effective secondary school administration. The study adopted a descriptive research design. The study population was 286 principals. The study sample was 229 principals drawn through a simple random sampling, representing 80% of the population. An instrument, principles and problems of policy implementation for effective secondary school administration was utilized for data collection. Cronbach alpha established a reliability coefficient of 0.89. Mean and standard deviation were used for data collection, while a t-test was utilized to test the hypotheses at a 0.05 significance level. The researchers found that the principles of policy implementation for effective secondary school administration are founded on ensuring a positive and clear policy statement, flexibility in the policy statement, fact-based policy statement, effectiveness in policy statement communication, openness to review, and properly documented in writing. It was recommended that school principals provide copies of the school policy to all the teachers. The principals should not be subjective in implementing policy for effective school administration. The implication of the study is that principals should adopt effective principles for policy implementation.